Pengaruh Customer Bonding dan Customer Experience Terhadap Loyalitas Pelanggan Shampo NR Kecamatan Medan Sunggal (Studi Kasus Pada PT. Ikapharmindo Putramas) - Putri Ezramia Pasaribu; Wan Rizca Amelia; Sugito Sugito (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
This purpose of study was to determine and analyze the effect of customer bonding and customer experience on customer loyalty of Shampoo NR at districts of medan sunggal (student case study of PT.Ikapharmindo Putramas Medan)’’. The research method used was exploratory research, where the variables were measured using a Likert scale. Methods of data collection is done by interview (interview), with a list of questions (questionair). population in this study were all NR Shampoo customers. totaling 57 people. Sampling with the saturated sampling method or better known as the census. In this study, the population was relatively small, as many as 57 people. Data processing using SPSS version 23 software, with descriptive analysis and hypothesis testing with multiple regression analysis. The results showed that: (1) partially customer bonding variables affect customer loyalty NR Shampoo at PT.Ikapharmindo Putramas Medan sunggal ; (2) partially customer experience variables affect customer loyalty NR Shampoo at PT.Ikapharmindo Putramas Medan sunggal; (3) At the same time, there is a significant positive impact between customer retention and customer experience. Customer Retention NR Shampoo PT. Ikapharmindo Putramas Medan